Fuerza de ley: sobre el poder y la violencia en Foucault y Hobbes - Raga Rosaleny, Vicente (Logos. Anales del Seminario de Metafísica, 2007)
In this article I try to make a brief critic analysis on the notion of power in Foucault’s works, and I pay special attention to some lessons that he taught in the Collegè de France in 1976. These lessons are translated in Spanish and collected in a book, Hay que defender la sociedad. First, I draw the main skills of power in Foucault, in contrast with sovereignty theory, as it is exemplified in Hobbes. Second, I will propose a “forced” re-reading of Hobbes works. I try to show that Hobbes are nearer Foucault than in the French philosopher interpretation. To conclude, I show some problems that Foucault and Hobbes share in a forced re-reading and propose some alternative answers to their problems.